Pelatihan Penerapan Gim Edukasi dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Swandi, Ahmad; Arsyad, Susalti Nur; Balalembang, Vinsen; Fansury, Andi Hamzah (FKIP UKI TORAJA, 2023)
The use of games has been widely used by elementary school students, but the games used are more entertainment in nature and do not have educational content. This training aims to implement educational games and find out students' perceptions of implementing educational games developed using the GDevelop application. The training participants were fourth grade students at SDN Lariang Bangi 1, Makassar City, for the 2022/2023 Academic Year, totaling 34 respondents. The training uses Goad model. Data collection techniques in the training used are questionnaires, interviews and documentation. The results of this training show that most of the students have been able to use educational games well, besides that students are very enthusiastic and motivated by the implementation of the educational games provided. the application questions in the game can help students to remember the material presented by the teacher. In addition, students also feel challenged when working on questions given by the teacher with a duration of time